Pendampingan Penentuan Harga Pokok Produksi Pada UMKM di Kota Jayapura - Waromi, Juliana; Muslimin, Ulfah Rizky; Tandililing, Elia Madatu; Paru, Sara Marlyn; Patty, Maria Apriane (UNIVERSITAS CENDERAWASIH, 2024)
This community service activity aims to provide an education as well as assistance for 10 (ten) MSME businesses regarding the concept of the Cost of Goods Manufactured (COGM), elements of COGM and the calculation process of COGM, so that each business actor is able to make a systematic financial bookkeeping and, ultimately, able to predict their potential gain or loss of their businesses. Keywords: Cost of Goods Manufactured, MSME businesses